Pentostatin for the treatment of indolent lymphoproliferative disorders - Ho, Anthony Dick; Hensel, Manfred (Seminars in hematology, 2006)
Purine analogues have been shown to be active in a variety of B- and T-cell malignancies. Among them, pentostatin is also a tight binding inhibitor of adenosine deaminase (ADA), a key enzyme of purine metabolism. ADA is present in all human tissues, with the highest levels in the lymphoid system. Early clinical trials with pentostatin used high doses for acute lymphoblastic leukemias, which were characterized by high levels of ADA. Through the efforts of a few investigators, low-dose regimens that are active and well tolerated for indolent lymphoid malignancies have been developed. Myelosuppressive adverse effects have been shown to be minimal using these schedules. Lymphoplasmacytic lymphoma (LL) is an indolent chronic B-cell lymphoproliferative disorder moderately responsive to alkylating agents. All of the purine analogues have shown activity in LL. However, the advantage of pentostatin over the other agents is the relatively specific toxicity to lymphoid cells and the paucity of myelosuppression as a single agent. No direct comparisons of the agents have been investigated, although pentostatin may be considered to be preferred since it has not been associated with toxicity to myeloid progenitors in colony assays. This is of significance for patients who might benefit from high-dose chemotherapy with autologous stem cell transplantation.